2015
DOI: 10.1099/jmm.0.000093
|View full text |Cite
|
Sign up to set email alerts
|

Association of oral streptococci community dynamics with severe early childhood caries as assessed by PCR-denaturing gradient gel electrophoresis targeting the rnpB gene

Abstract: This study sought to investigate the possible association between the dynamics of oral streptococci community profiles and severe early childhood caries (S-ECC) development, compared with caries-free (CF) controls. Supragingival plaque samples were evaluated from 8-32-month-old children who had previously been assessed for overall profiles of their oral microbial community. Twelve children were in each group. Bacterial genomic DNA was extracted and amplified using rnpB-specific primers for streptococci; the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…S. gordonii , as the initial colonizers of dental biofilms, is thought to help to inhibit the occurrence of dental caries (Cheng et al., 2020). The study has shown that there is a negative correlation between dental caries and the detection rate of S. gordonii (Tao et al., 2015). Although we have not determined the correlation between vicR expression of S. mutans and dental caries, it can affect the growth of S. gordonii , which also has important clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…S. gordonii , as the initial colonizers of dental biofilms, is thought to help to inhibit the occurrence of dental caries (Cheng et al., 2020). The study has shown that there is a negative correlation between dental caries and the detection rate of S. gordonii (Tao et al., 2015). Although we have not determined the correlation between vicR expression of S. mutans and dental caries, it can affect the growth of S. gordonii , which also has important clinical significance.…”
Section: Discussionmentioning
confidence: 99%